The Use of WhatsApp in English Writing Activities: A Correlational Study of the Use of WhatsApp and the Writing Performance - Tanashur, Panji; Aprianto, Dedi; Sutarman; Rahmawati, Lela (SALEE: Study of Applied Linguistics and English Education, 2024)
There are differences of opinion arising from the results of research on the use of WhatsApp in ELT. The results revealed that the use of WhatsApp software contributed positively to the development of English writing proficiency, and the other results considered that the use of WhatsApp has many weaknesses and difficulties in writing and other language instructions. This controversy allowed the researcher to conduct research aimed at finding out whether there was a correlation between the use of WhatsApp as a tool in writing activities and EFL student writing performance and to find out how close the relationship between the two variables is. The statistical correlation from Pearson Product Moment revealed that the correlation of the independent variable (X) with the dependent variable (Y) showed a sig. value of 0.000 < 0.05, and the correlation rate was very strong with a correlation coefficient (r = 0.832), along with the hypothesis tested showing Ho: ?1 ? 0. This study shows a very strong correlation between the use of WhatsApp as a tool in English writing activities and writing performance. WhatsApp interventions into ELT in the form of group WhatsApp and individual WhatsApp’s text message interactions have contributed to EFL students’ writing skills as the correlation of two variables goes parallel. The more students do the writing activity through WhatsApp, the higher the writing achievement they acquire.